Morphological And Syntactic Errors Found In English Composition Written By The Students Of Daarut Taqwa Islamic Boarding School Klaten - Rachmat Faisyal, Rachmat, Prof. Dr. Endang Fauziati, M. Hum, Dr. Dwi Haryanti, M.Hum (2015)
Error analysis is a type of linguistic analysis that focuses on the errors learners make. It consists of a comparison between the errors made in the target language and that target language it self. This research focuses on errors in narrative English writing written by the students of grade five of KMI Islamic boarding school in Klaten (equal with grade eleven of senior high school) in order to know their classification of errors. The errors found in this research are classified into morphological and syntactic errors as the result of their effort to study the target language. The findings of the research show that the students create more errors in syntax rather than in morphology with different sources of errors, those are: language transfer, strategies of second language learning and overgeneralization. The findings also show that overgeneralization is the biggest source of errors, followed by strategies in second language learning and the least is language transfer. Based on the findings found in this research, it is hoped that it would trigger other researchers to build up further discussion and research on errors in this subject with the broader aspect and different subjects.